Synthesis, characterization and antimicrobial activity of poly(2-acrylamido-2-methyl-1-propanesulfonic acid-co-crotonic acid) - Soykan, Cengiz; Coskun, Ramazan; Kirbag, Sevda; Sahin, Ertan (Taylor & Francis Inc, 2007)
2-Acrylamido-2-methyl-1-propanesulfonic acid ( AMPS), and crotonic acid (CrA) copolymerized with different feed ratios using N,N-dimethylformamide as a solvent and benzoyl peroxide (Bz(2)O(2)) as an initiator at 70 degrees C. Structure and composition of copolymers for a wide range of monomer feed were determined by elemental analysis ( content of N for AMPS-units). Monomer reactivity ratios for AMPS (M-1)- CrA (M-2) pair were determined by the application of conventional linearization methods such as Fineman-Ross (F-R), Kelen-Tudos (KT) and Extended Kelen-Tudos (EKT) and a nonlinear error invariable model method using a computer program RREVM. The characterizations were done by Fourier transform infrared spectroscopy (FTIR), H-1- and C-13-NMR spectroscopy, differential scanning calorimetry (DSC) thermal gravimetry analysis (TGA), scanning electron microscopy (SEM), and X-ray diffraction. The antimicrobial effects of polymers were also tested on various bacteria, and yeast.
Keywords: poly(2-acrylamido-2-methyl-1-propanesulfonic acid-co-crotonic acid); thermogravimetric analysis; SEM analysis; monomer reactivity ratios; X-ray diffractions